(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper explores the therapeutic power of writing as depicted in Ian McEwan's novels "Atonement" and "Black Dogs." In "Atonement," the protagonist Briony Tallis uses writing as a means to atone for her past mistakes, seeking personal redemption through the narrative reconstruction of events. Her journey underscores the cathartic effect of storytelling, highlighting how the act of writing can serve as a tool for self-exploration and emotional healing. Similarly, in "Black Dogs," the characters grapple with their traumatic pasts, and writing becomes a conduit for understanding and processing their experiences. This paper examines how McEwan portrays the psychological benefits of writing, demonstrating its capacity to heal emotional wounds and foster a deeper understanding of oneself and others. By analyzing key passages and character developments, the study reveals how McEwan intricately weaves the theme of therapeutic writing into his narratives, offering insights into the broader implications of literature as a means of coping with trauma and guilt. Through this exploration, the paper aims to underscore the enduring significance of writing as a powerful therapeutic tool in contemporary literature.